An investigation into the feasibility and potential benefits of shared taxi services to commuter stations - Steve Wright (Urban, Planning and Transport Research, 2014)
Parking is a serious problem at many rail stations where large numbers of commuters ‘park and ride’ mainly on a single occupancy basis. In many cases, these stations are not designed for mass parking, resulting in on-street parking conflicts with residents and local commercial businesses. Furthermore, congestion around stations is a growing problem, compounded by rail passengers being picked up by friends or relatives resulting in queues of waiting cars at station entrances. These ‘kiss and ride’ trips require double the fuel (home to station to home again) and impinge on the time of the driver providing the lift. In this paper, it is anticipated that the introduction of shared taxis to rail stations has the potential to relieve these parking and congestion problems while also providing an affordable extra service to the rail station for those without access to a car or other suitable public transport service. A model for shared taxi operation is presented and the potential viability and benefits of such a service is illustrated using data from two varied case study sites: (1) a station in South East England providing rail access to London and (2) a smaller station in Central Scotland providing rail access to Edinburgh.